2009
DOI: 10.2174/092986609787847983
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of the Altitude Adapted Hemoglobin of Guinea Pig

Abstract: Hemoglobin is the versatile oxygen carrier in the blood of vertebrates and a key factor for adaptation to live in high altitudes. Several structural changes are known to account for increased oxygen affinity in hemoglobin of altitude adapted animals such as llama and barheaded goose. Guinea pigs are adapted to live in high altitudes in the Andes and consequently their hemoglobin has an increased oxygen affinity. However, the structural changes responsible for the adaptation of guinea pig hemoglobin are unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The α-chain of guinea pig hemoglobin shares 75% identical amino acids with human hemoglobin, while the β-chain is identical with its counterpart in human hemoglobin in 65% of the positions. Absorption spectroscopy of dissolved crystals indicated that guinea pig hemoglobin crystallized as met-hemoglobin [27]. The active site and its surrounding amino acids are typical in comparison with other hemoglobins in the met state.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The α-chain of guinea pig hemoglobin shares 75% identical amino acids with human hemoglobin, while the β-chain is identical with its counterpart in human hemoglobin in 65% of the positions. Absorption spectroscopy of dissolved crystals indicated that guinea pig hemoglobin crystallized as met-hemoglobin [27]. The active site and its surrounding amino acids are typical in comparison with other hemoglobins in the met state.…”
Section: Resultsmentioning
confidence: 95%
“…Crystal parameters have been reported before [27]. The structure solution was obtained by molecular replacement with carbonmonoxy horse hemoglobin (PDB-code: 2D5X) as starting model, using the program PHASER implemented in the CCP4 suite [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation